Chitetezo Cooperative Federation: Capacity building report January to June 2023 - Zulu, Samuel (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The objective of this report is to highlight the capacity-building activities conducted by the Community Market for Conservation (COMACO) through the Chitetezo Cooperative Federation (CCF) in collaboration with the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). Capacity building activities focused on the following trainings: (i) Crop market workshops with stakeholders; (ii) Cashier or literacy trainings; (iii) chiefdom or cooperative Training on Crop markets; (iv) Field day activities; and (iv) Agroforestry trainings.